Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1246/cl.1997.885
|View full text |Cite
|
Sign up to set email alerts
|

Tanzawaic Acids A, B, C, and D: Inhibitors of Superoxide Anion Production from Penicillium citrinum

Abstract: Tanzawaic acids have been isolated from Penicillium citrinum and their structures were elucidated by spectroscopic analysis. Their relative stereochemistries were also clarified by detailed analyses of 1H–1H coupling constants and NOE data. Tanzawaic acid B (GS-1302-1) significantly inhibits superoxide anion production in human neutrophils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 2 publications
1
40
0
Order By: Relevance
“…Results revealed that compound 1 possess a pronounced antioxidant activity with IC 50 value of 2.8 μM (compared to quercetin which possesses IC 50 of 5.72 μM). This antioxidant activity was similar to its related congeners tanzawaic acid A−D . Moreover, compound 1 proved to have a weak antibacterial activity against Staphylococcus aureus with a MIC of 64 μg/mL and no cytotoxic effect.…”
Section: Resultssupporting
confidence: 52%
“…Results revealed that compound 1 possess a pronounced antioxidant activity with IC 50 value of 2.8 μM (compared to quercetin which possesses IC 50 of 5.72 μM). This antioxidant activity was similar to its related congeners tanzawaic acid A−D . Moreover, compound 1 proved to have a weak antibacterial activity against Staphylococcus aureus with a MIC of 64 μg/mL and no cytotoxic effect.…”
Section: Resultssupporting
confidence: 52%
“…[2][3][4][5][6][7][8] Structurally, these compounds possess a highly reduced polyunsaturated octaketide backbone derived from the condensation of 8 mol of acetate, plus the addition of two methyl groups at C-8 and C-10, predictably from methionine, as frequently occurs in fungal metabolism. 2,5,7,8 Here we describe the chemical structure and relative stereochemistry, propose a biogenetic hypothesis and investigate the antimicrobial and cytotoxic activities of four novel tanzawaic acids M-P (1-4) (Fig. Some of these compounds display anticoccidial activity, inhibition of superoxide anion production, inhibition of NO production or inhibition of protein tyrosine phosphatase 1B (PTP1B).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these compounds display anticoccidial activity, inhibition of superoxide anion production, inhibition of NO production or inhibition of protein tyrosine phosphatase 1B (PTP1B). 2,3 Results and discussion 1).…”
Section: Introductionmentioning
confidence: 99%
“…Next, we investigated the possibility of selectively identifying sulfur compounds from a mixture containing 1.0 mg each of six microbial compounds: outovirin A and nanaomycin K as sulfur compounds, and acremolin B [21], SF-227 [22], beauvericin [23] and tanzawaic acid B [24] as non-sulfur compounds. This mixture was oxidized as described above using H 2 O 2 and (NH 4 ) 6 Mo 7 O 24 •4H 2 O as a catalyst.…”
Section: Resultsmentioning
confidence: 99%